2004
DOI: 10.1063/1.1739131
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and strength of metal oxide high-temperature superconductors (Review)

Abstract: The results of research on the plasticity and strength of a wide class of metal oxide perovskite-like compounds which have the property of high-temperature superconductivity or which can be used as base compounds for making high-temperature superconductors (HTSCs) are systematized and presented from a unified point of view. The mechanical properties of materials with different morphology—single crystals, polycrystals, and composites,—measured by different methods of mechanical testing in the low-temperature, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 155 publications
0
9
0
Order By: Relevance
“…This phase is highly anisotropic, being confined to the ab-plane. Lubenets et al [28] reported that strong covalent and ionic bonds create high Peierls barriers, which constrain dislocation mobility in YBaCuO single crystals. Indentation depth, h (nm) Fig.…”
Section: Microstructure Of Ybacuo Samplesmentioning
confidence: 99%
“…This phase is highly anisotropic, being confined to the ab-plane. Lubenets et al [28] reported that strong covalent and ionic bonds create high Peierls barriers, which constrain dislocation mobility in YBaCuO single crystals. Indentation depth, h (nm) Fig.…”
Section: Microstructure Of Ybacuo Samplesmentioning
confidence: 99%
“…Therefore, the study of mechanical properties of these compounds, such as of the hardness (H), elastic modulus (E) and fracture toughness (K IC ), is very crucial [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Polycrystalline LaFeAsO 0.9 F 0.1 was synthesized by heating a mixture of lanthanum arsenide, iron arsenide, and dehydrated La 2 O 3 powders in silica tube filled with Ar gas at 1527 K for 40 h. F -ion doping was performed by adding mixture of LaF 3 and La at the ratio of 1:1 to the starting powder.…”
Section: Methodsmentioning
confidence: 99%
“…One of the important subfields of the high-T c superconductors is the study of the plasticity and strength for practical application as devising and for manufacturing high-quality objects. While metal oxide ceramics is brittle in the region of moderately low temperatures due to its high Peierls stress, a ceramic can manifest significant ductility 2,3) and even superplasticity, which is due to grain boundary diffusion, dislocation motion and grain boundary sliding, at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%